TINJAUAN KRIMINOLOGI MEMASUKI ATAU MENYUSUP KEDALAM SUATU JARINGAN KOMPUTER SECARA TIDAK SAH MENURUT UU NO.11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - kurniawan kurniawan sihaloho; Josua Josua Sitohang; Bella Bella Fazrina (jurnal.unprimdn.ac.id, 2019)
This research has an information technology background that plays an important role in human life both in the present and in the future. The internet can penetrate the boundaries between countries and accelerate the spread and exchange of knowledge both among scientists or scholars throughout the world. Behind the ease of use of the internet, there is a dark side that worries the users, namely in terms of security. Public and global internet networks are very vulnerable to various forms of crime. The actions taken by the government to overcome in terms of reducing crime activities enter or infiltrate into a computer network illegally is the issuance of Law NO.11 of 2008 concerning Information and Information Transactions can be interpreted as a crime committed by a person or group of people with the intention of taking the advantage of others through a computer network. This study uses legal normative juridical research. The purpose of this study was to find out how the modus operandi and how prevention efforts enter or infiltrate into a computer network illegally. The mode is carried out with the intention of sabotage or theft of important and confidential information. Criminology review aims to investigate the widest possible crime symptoms. crime as needed prevention efforts are preventive (prevention) before the crime occurs and (eradication) after the crime has occurred is (refresive).